Transformational Leadership and Competence as Predictors of Bos Fund Manager's Performance : The Mediating Role of Organizational Commitment - Ni Made Dwi Yanti; Gusti Ayu Sugiati; Ida Ayu Surasmi; Ni Luh Putu Indiani; A.A Media Martadiani; Ida Bagus Udayana Putra (Husnayain Business Review, 2026)
This study aims to analyze the influence of transformational leadership and competence on the performance of the management of School Operational Assistance Funds (BOS) at State Vocational Schools in Buleleng Regency, with organizational commitment as a mediating variable. BOS Fund management requires accountability, transparency, and compliance with regulations, so adequate leadership factors and human resource capacity are needed to improve performance. This study uses a quantitative approach with Structural Equation Modelling analysis techniques based on Partial Least Squares (SEM-PLS). The research population is all BOS Fund managers in 14 State Vocational Schools in Buleleng Regency, with a total of 56 respondents. The results of the study show that transformational leadership and competence have a positive and significant effect on the performance of BOS Fund management. In addition, transformational leadership and competence also have a positive and significant effect on organizational commitment. Organizational commitment has been proven to have a positive effect on performance and partially mediate the influence of transformational leadership and competence on the performance of BOS Fund management. These findings confirm that the improvement of BOS Fund management performance is not only determined by technical factors, but also by leadership aspects and organizational commitment as psychological mechanisms that strengthen performance.